Effect of Shear Wall Placement Variations on Seismic Response of Reinforced Concrete Dual-System Buildings - Puspita Rahmasari; Chandra Alip Pratama; Qalbi Hafiyyan (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
The seismic performance of reinforced concrete dual-system buildings is highly impacted by the shear wall position, particularly in seismic risk-prone and soft soil regions such as Jakarta, Indonesia. This study examines the influence of shear wall layout diversity on the elastic seismic response of a 15-story reinforced concrete dual-system building. Five structural models were developed in finite-element structural analysis software, consisting of one model without shear walls (N-SW) and four models with identical shear wall areas yet different layouts: diagonal corner (DC-SW), core (C-SW), four-corner (FC-SW), and mid-side (MS-SW). The seismic response was assessed using response spectrum analysis by comparing the fundamental period, modal mass participation ratio, lateral displacement, lateral stiffness, inter-story drift, and internal forces in columns and shear walls. All of the structural models containing shear walls satisfied the dual-system requirements, while the N-SW was not classified as a dual-system structure. All models likewise complied with the inter-story drift limits specified in SNI 1726:2019. Nevertheless, their seismic responses varied depending on the adopted shear wall layout. The core configuration generally exhibited the highest lateral stiffness, the shortest fundamental period, and the lowest lateral displacement. It also reduced the bending moment and shear force demands in the columns. These outcomes indicate that the location of shear walls governs the seismic force transfer and the overall behavior of reinforced concrete dual-system buildings.